Similar Inflammatory Responses following Sprint Interval Training Performed in Hypoxia and Normoxia - Richardson, Alan J.; Relf, Rebecca L.; Saunders, Arron; Gibson, Oliver R. (Frontiers in Physiology, 2016)
Sprint interval training (SIT) is an efficient intervention capable of improving aerobic capacity and exercise performance. This experiment aimed to determine differences in training adaptations and the inflammatory responses following 2 weeks of SIT (30s maximal work, 4 min recovery; 4-7 repetitions) performed in normoxia or hypoxia. Forty-two untrained participants [(mean ± SD), age 21 ±1 yrs, body mass 72.1 ±11.4 kg and height 173 ±10 cm] were equally and randomly assigned to one of three groups; control (CONT; no training, n = 14), normoxic (NORM; SIT in FiO2: 0.21, n = 14) and normobaric hypoxic (HYP; SIT in FiO2: 0.15, n = 14). Participants completed a V̇O2peak test, a time to exhaustion (TTE) trial (power = 80% V̇O2peak) and had haematological [haemoglobin (Hb), haematocrit (Hct)] and inflammatory markers [interleukin-6 (IL-6), tumor necrosis factor-α (TNFα)] measured in a resting state, pre and post SIT. V̇O2peak (mL.kg-1.min-1) improved in HYP (+11.9%) and NORM (+9.8%), but not CON (+0.9%). Similarly TTE improved in HYP (+32.2%) and NORM (+33.0%), but not CON (+3.4%) whilst the power at the anaerobic threshold (AT; W.kg-1) also improved in HYP (+13.3%) and NORM (+8.0%), but not CON (-0.3%). AT (mL.kg-1.min-1) improved in HYP (+9.5%), but not NORM (+5%) or CON (-0.3%). No between group change occurred in 30 s sprint performance or Hb and Hct. IL-6 increased in HYP (+17.4%) and NORM (+20.1%), but not CON (+1.2%) respectively. TNF-α increased in HYP (+10.8%) NORM (+12.9%) and CON (+3.4%). SIT in HYP and NORM increased VO2peak, power at AT and TTE performance in untrained individuals, improvements in AT occurred only when SIT was performed in HYP. Increases in IL-6 and TNFα reflect a training induced inflammatory response to SIT; hypoxic conditions do not exacerbate this.